Die afrikanischen Arten der Gattungsgruppe 'Amytta' Karsch (Saltatoria: Tettigoniidae, Meconeminae). - Beier, Max Walter Peter (Contributions to Entomology = Beiträge zur Entomologie, 1965)
Having studied extensive material from twelve museums and institutes with a total of 251 specimens, and having reexamined all types, several of which proved to be synonyms, we now distinguish within the genus group "Amytta" Karsch 34 African species and two subspecies. Of these, 25 species and two subspecies are described as new. The species belong to nine genera, seven of which are newly established. The group seems to be con-centrated in tropical West Africa and Central Africa, in regions more or less covered by forests. The forms are all relatively small and of marked habitual uniformity, while the sexes differ chiefly in the formation of the final segments and their appendages, particularly the male cerci. A key for the determination of all genera, species and subspecies is given. Nomenclatural Actsangulata Chopard, 1945 (Amytta), syn. n. of Amyttosa mutillata (Karsch, 1890)occidentalis Karsch, 1890 (Amytta), syn. n. of Amyttosa mutillata (Karsch, 1890), male, nec femaleukamica Beier, 1965 (Amytta), spec. n.angolensis Beier, 1965 (Amyttacta), spec. n.rhodesica Beier, 1965 (Amyttacta), spec. n.manuata Beier, 1965 (Amyttella), spec. n.pusillula Beier, 1965 (Amyttella), spec. n.congica Beier, 1965 (Amyttina), spec. n.dispersa Beier, 1965 (Amyttina), spec. n.exorbitans Beier, 1965 (Amyttina), spec. n.kivuensis Beier, 1965 (Amyttina), spec. n.rhodei Beier, 1965 (Amyttina), spec. n.schoutedeni Beier, 1965 (Amyttina aliquantula), sspec. n.forcipata Beier, 1965 (Amyttopsis), spec. n.podicaelata Beier, 1965 (Amyttopsis), spec. n.vinculata Beier, 1965 (Amyttopsis), spec. n.bicaudata Beier, 1965 (Anepitacta), spec. n.guineensis Beier, 1965 (Anepitacta), spec. n.nigerica Beier, 1965 (Anepitacta), spec. n.scrofina Beier, 1965 (Anepitacta), spec. n.katangica Beier, 1965 (Anepitacta nigerica), sspec. n.eburnea Beier, 1965 (Proamytta), spec. n.kamerunensis Beier, 1965 (Proamytta), spec. n.reducta Beier, 1965 (Proamytta), spec. n.simillima Beier, 1965 (Proamytta), spec. n.simplicoides Beier, 1965 (Proamytta), spec. n.sincera Beier, 1965 (Proamytta), spec. n.Amyttacta Beier, 1965 (Tettigoniidae), gen. n.Amyttella Beier, 1965 (Tettigoniidae), gen.n.Amyttina Beier, 1965 (Tettigoniidae), gen. n.Amyttopsis Beier, 1965 (Tettigoniidae), gen. n.Amyttosa Beier, 1965 (Tettigoniidae), gen. n.Gonamytta Beier, 1965 (Tettigoniidae), gen. n.Proamytta Beier, 1965 (Tettigoniidae), gen. n.bubianus I. Bolívar, 1906 (Xyphidiopsis), syn. n. of Amyttosa mutillata (Karsch, 1890)mitratus (female) I. Bolívar, 1906 (Xyphidiopsis), syn. n. of Amyttosa mutillata (Karsch, 1890)mitratus (male) I. Bolívar, 1906 (Xyphidiopsis), syn. n. of Gonamytta occidentalis (Karsch, 1889), female